Religious literacy: information search regarding Islam among virtual citizens and role of contemporary preaching / Aini Faezah Ramlan … [et al.] - Ramlan, Aini Faezah; Suyurno, S Salahudin; Misman, Juritah; Kertamukti, Rama (Academy of Contemporary Islamic Studies (ACIS), 2024)
The issue of religious literacy and information search regarding Islam has become a trending topic among virtual citizens, especially among the younger generation. The younger generation is synonymous to virtual citizen and social media platforms such as IG, Telegram, Twitter, YouTube, Tik Tok, Instagram, WhatsApp, Facebook and many more. This article aims to present (1) the role of preaching in terms of religious literacy and the search for information regarding Islam among virtual citizens, as well as (2) ways to approach contemporary preaching in social media platforms. This study uses qualitative research methods through library research. Results showed that the level of religious literacy among social media users affected the acceptance and reliability of false or inaccurate religious information. Consequently, social media users could easily be influenced in heretical teachings if they learn religion and get information about religion from sources which are unauthentic such as from random social media platforms. Social media users who lack Islamic knowledge, particularly Muslim youths may face problems to determine the validity of information resources. In fact, Islam prohibits the dissemination of untruthful information. Essentially, Muslims must practice Tabbayyun. Tabbayun directs the attitude of doing vigilant checking and researching of any information to keep away from information which could harm our believes and perspectives